2012
DOI: 10.4103/0975-7406.100245
|View full text |Cite
|
Sign up to set email alerts
|

Lasers in periodontics

Abstract: Laser is one of the most captivating technologies in dental practice since Theodore Maiman in 1960 invented the ruby laser. Lasers in dentistry have revolutionized several areas of treatment in the last three and a half decades of the 20th century. Introduced as an alternative to mechanical cutting device, laser has now become an instrument of choice in many dental applications. Evidence suggests its use in initial periodontal therapy, surgery, and more recently, its utility in salvaging implant opens up a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…(21) The laser eliminates the need for a post-surgical dressing after traditional gingivectomy. (22) Histologically, in the biopsy taken after 7 days, less infiltration of inflammatory cells had been seen in laser with a good improved epithelization, which result in reducing the scars and the contraction of the wound and thus improve the healing (9).…”
Section: Discussionmentioning
confidence: 99%
“…(21) The laser eliminates the need for a post-surgical dressing after traditional gingivectomy. (22) Histologically, in the biopsy taken after 7 days, less infiltration of inflammatory cells had been seen in laser with a good improved epithelization, which result in reducing the scars and the contraction of the wound and thus improve the healing (9).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of action of lasers in hard and soft dental tissues depend directly on the absorption of light by the chromophore in the target tissue. Er:YAG lasers are a noninvasive modality, effective to promote bone recontouring in surgical procedures for clinical crown lengthening (Elavarasu,, Naveen., & Thangavelu., 2012;Deeb et al, 2019). These findings corroborate the studies by Chen et al (2016) and Koppolu et al (2017) in which it was observed that the use of the Er:YAG laser was less traumatic for dental hard and soft tissues when compared to the traditional surgical procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, in the field of dentistry, the antimicrobial effectiveness of Aloe vera was tested, where it was proved to be effective against various microorganisms. 43 An animal study evaluated the antimicrobial activity of Aloe vera against microbes like Streptococcus mutans , Enterococcus faecalis , Candida albicans . They had also assessed the pulp cell viability when used as a direct pulp capping agent in rats, and they reported that fibroblast and osteoblast present in the dentin–pulp complex were viable after 24 hours.…”
Section: Discussionmentioning
confidence: 99%